Razonabilidad de los estados financieros del año 2018 de la Constructora Carrasco & Murillo “Aldaestructure S.A. - Santillan Delgado, Julio Armando (2020)
The profitability of the company is very good according to the financial reasons used, it was observed that the balances presented to the regulatory entities are at zero values, however, when requesting the physical information from the institution, which was transferred in the most friendly way and when verifying, it could be verified that the balances are with very significant values that when making the respective substitutes would generate a very high tax to pay for the high amounts that are in the balances, values that in the following fiscal period will be an expense for the company since they will have to pay, in addition to the tax, the respective fines and interest, for not performing at the time they should have done so.